2000
DOI: 10.1103/physrevc.61.044324
|View full text |Cite
|
Sign up to set email alerts
|

Level density andγstrength function in162Dyfrom inelastic3

Abstract: Complementary measurements have been performed for the level density and γ strength function in 162 Dy using inelastic 3 He scattering. Comparing these results to previous measurements using the 163 Dy( 3 He,α) reaction, reveals that the measured quantities above 1.5 MeV do not depend significantly on the nuclear reaction chosen. PACS number(s):

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
3
14
1
Order By: Relevance
“…The results obtained with the very different reactions ( 3 He,α) and ( 3 He, 3 He ′ ), are almost identical, except for the level density of the ground state band in 162 Dy. Here, the ( 3 He, 3 He ′ ) reaction overestimates the level density, as has been discussed previously [4].…”
Section: Experimental Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…The results obtained with the very different reactions ( 3 He,α) and ( 3 He, 3 He ′ ), are almost identical, except for the level density of the ground state band in 162 Dy. Here, the ( 3 He, 3 He ′ ) reaction overestimates the level density, as has been discussed previously [4].…”
Section: Experimental Methodssupporting
confidence: 69%
“…(4) are listed in Table I. The level densities for the three reactions previously published [3,4,7] deviate slightly since we here have used updated and newly recommended data [15,16]. The results obtained with the very different reactions ( 3 He,α) and ( 3 He, 3 He ′ ), are almost identical, except for the level density of the ground state band in 162 Dy.…”
Section: Experimental Methodsmentioning
confidence: 83%
“…It has been shown that the measured total γ-ray spectrum of the 161 Dy(n, γ) [20]. These results strongly support the statistical model for the radiative decay in these reactions and the correctness of the extraction procedure for level densities and RSFs in the case of the 3 He induced reactions.…”
Section: Possible Systematic Errors and Other Considerationssupporting
confidence: 68%
“…More details on this effect are given in Ref. [22]. Except for this effect, the agreement between level densities for the same nucleus obtained via two different reactions is excellent.…”
Section: Level Densitiesmentioning
confidence: 87%